Hematopoiesis from human embryonic stem cells: overcoming the immune barrier in stem cell therapies. - Priddle, H; Jones, DR; Burridge, P; Patient, R (2006)
The multipotency and proliferative capacity of human embryonic stem cells (hESCs) make them a promising source of stem cells for transplant therapies and of vital importance given the shortage in organ donation. Recent studies suggest some immune privilege associated with hESC-derived tissues. However, the adaptability of the immune system makes it unlikely that fully differentiated tissues will permanently evade immune rejection. One promising solution is to induce a state of immune tolerance to a hESC line using tolerogenic hematopoietic cells derived from it. This could provide acceptance of other differentiated tissues from the same line. However, this approach will require efficient multilineage hematopoiesis from hESCs. This review proposes that more efficient differentiation of hESCs to the tolerogenic cell types required is most likely to occur through applying knowledge gained of the ontogeny of complex regulatory signals used by the embryo for definitive hematopoietic development in vivo. Stepwise formation of mesoderm, induction of definitive hematopoietic stem cells, and the application of factors key to their self-renewal may improve in vitro production both quantitatively and qualitatively.